FAMILY AND SCHOOLS COLLABORATION IN SUPPORTING CHILDREN WITH SPECIFIC LEARNING DISORDERS - Zikril Maulana Zikril; Sri Nurhayati Selian Selian (International Journal of Multidisciplinary Reseach, 2026)
Children with Specific Learning Disorder (SLD) often experience difficulties in basic academic skills such as reading, writing, and arithmetic, which can impact their learning development and adjustment in the school environment. Effective support for children with SLD requires the involvement of various parties, especially families and schools, through ongoing collaboration. This study aims to explore the forms of collaboration between families and schools in supporting children with Specific Learning Disorder. This study used a qualitative approach with in-depth interviews with four participants: two parents of children with SLD and two teachers directly involved in the child's education process. The research data were analysed using thematic analysis to identify patterns of experience, forms of collaboration, and communication dynamics between families and schools. The results showed that collaboration between parents and teachers is realized through communication regarding children's learning development, coordination in the implementation of learning strategies, and emotional support provided to children. However, this study also identified several challenges in collaboration, such as limited communication time and differences in understanding of children's needs. This study emphasizes the importance of strengthening partnerships between families and schools to create more effective learning support for children with Specific Learning Disorder.